2019
DOI: 10.1128/aac.00680-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of the msaABCR Operon in Cell Wall Biosynthesis, Autolysis, Integrity, and Antibiotic Resistance in Staphylococcus aureus

Abstract: Staphylococcus aureus is an important human pathogen in both community and health care settings. One of the challenges with S. aureus as a pathogen is its acquisition of antibiotic resistance. Previously, we showed that deletion of the msaABCR operon reduces cell wall thickness, resulting in decreased resistance to vancomycin in vancomycin-intermediate S. aureus (VISA). In this study, we investigated the nature of the cell wall defect in the msaABCR operon mutant in the Mu50 (VISA) and USA300 LAC methicillin-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
(127 reference statements)
0
17
0
Order By: Relevance
“… 14 Any compromise of the cell wall plays an integral part in antibiotic resistance, because it is targeted by many antibiotics, including β-lactams (oxacillin), glycopeptides (vancomycin and teicoplanin) and other cell wall-associated antibiotics (daptomycin). 15 , 16 Vancomycin interferes with late-stage peptidoglycan synthesis by forming non-covalent hydrogen bonds with the penultimate d -Ala- d -Ala residues of newly synthesized UDP-MurNAc-pentapeptides, thereby disrupting downstream peptidoglycan assembly, cell wall synthesis is ultimately inhibited. 17 VISA strains share some common characteristics, including thickened cell wall, decreased autolytic activity, reduced cross-linking of peptidoglycan, slower growth rate and attenuated virulence.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Any compromise of the cell wall plays an integral part in antibiotic resistance, because it is targeted by many antibiotics, including β-lactams (oxacillin), glycopeptides (vancomycin and teicoplanin) and other cell wall-associated antibiotics (daptomycin). 15 , 16 Vancomycin interferes with late-stage peptidoglycan synthesis by forming non-covalent hydrogen bonds with the penultimate d -Ala- d -Ala residues of newly synthesized UDP-MurNAc-pentapeptides, thereby disrupting downstream peptidoglycan assembly, cell wall synthesis is ultimately inhibited. 17 VISA strains share some common characteristics, including thickened cell wall, decreased autolytic activity, reduced cross-linking of peptidoglycan, slower growth rate and attenuated virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Most drugs used for controlling S. aureus -related infections target cell wall biosynthesis, and increased peptidoglycan cross-linking is believed to contribute to the acquirement of drug-resistant capability. It has been observed that decreased peptidoglycan cross-linking leads to increased susceptibility toward cell-wall-targeting antibiotics, namely β-lactams and vancomycin [ 48 , 49 ]. Our transcriptome results, suggesting the over-expression of cell wall biosynthetic pathways, including penicillin-binding proteins, imply another way for the up-regulation of antibiotic resistance in S. aureus and C. albicans dual-species biofilms ( Figure 4 a,b and Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…MurA (UDP-N-acetylglucosamine 1-carboxyvinyltransferase), in the first committed step of peptidoglycan biosynthesis, catalyzes the transfer of enolpyruvate from phosphoenolpyruvate to UDP-NAG, releasing inorganic phosphate[35]. The deletion/inactivation of murA gene from S. aureus and Streptococcus pneumoniae has been reported to be lethal for bacteria due to the loss of cell integrity and susceptibility to osmotic lysis[36]. The importance of MurA as a drug target is also substantiated by the fact that the antibacterial activity of an antibiotic, fosfomycin is due to its covalent binding to the active site of MurA enzyme [37, 38].…”
Section: Discussionmentioning
confidence: 99%